Model Pemanfaatan Air di SMPN 28 Bandung sebagai Peraih Penghargaan Adiwiyata di Kota Bandung - A Hadian Pratama Hamzah; Nurhasanah Nurhasanah; Rini Soemarwoto (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
Water is a very important component in supporting life. Water conditions in the country is currently experiencing a lot of problems . Along with the increasing growth in the number of human increasing water demand, while water availability decreases. Adiwiyata Award-Winning School is a school that is considered successful in creating the management and conservation of the environment in terms of one aspect of saving water resources in the school. The aims of research are (i) to determine the efforts made to conserve water consumption in school, (ii) to knowing the water management system and water balanc , and (iii) the factors that influence the success of water conservation programs in schools. The method used is a mix between qualitative and quantitative method . Qualitative methods are used to determine school policy to conserve water consumption , and water management systems in schools . Quantitative methods are used to determine the water balance and the factors that influence the success of water conservation programs in school. The results showed in an effort to conserve water consumption in schools developed policies based management and environmental conservation contained in the vision, mission , goals and objectives of the program , funding policies and programs in policy development RAKS for water-saving infrastructure. Water management system prepared through a phase of water conservation programs, planning activities and implementation of water conservation, the school has not made the of the evaluation phase of the program . Water balance at SMP 28 obtained the consumption of water used is still below with SNI standard The largest volume of water consumption is used for activities wudhu , urination and hand washing. Savings occur from the use of waste water from wash hands and wudhu, thereby reducing water consumption in school..